Centering Gender in the Era of Digital and Green Transition Intersectional Perspectives - Drucza, Kristie; Kaddour, Amira; Ganguly, Sujata; Sarea, Adel M. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This edited volume examines the importance of centering gender in research and policymaking focused on climate change, environmental sustainability, and digital technology. Chapters unpack how the transition to a green and digital future affects various fields and industry sectors including STEM, agriculture, and energy, as well as why gender-transformative approaches-particularly the production and analysis of gender-inclusive disaggregated data-should be included in those transitions. The editors and authors also look at the positive impact of these considerations on economic growth and poverty eradication. Finally, this book presents an ideal/utopian view of what a gender-equal and inclusive world that has transitioned to green industries and embraced digital technologies might look like. This book will be of interest to scholars, researchers, students and policymakers across the Social Sciences including Sociology, Anthropology, Gender Studies, Science & Technology Studies, and Economics.
1. Introductory Chapter. Gendered Challenges in the Digital and Green Transition: An Intersectional Exploration -- Part I Global Challenges -- 2. Gender Within the SDGs Agenda: Importance and Intersectionality -- 3. Gender Inequalities, Poverty, And Disparities: Impact And Links In The Era Of Digital Transformations And Green Transition -- 4. Considering Climate Change Mitigation And Adaptation Through A Gendered Lens -- Part II A Sectorial Vision -- 5. Gendered Considerations In Relation To Climate Change And Agriculture: Reflections On Impact, Funding, And Mainstreaming -- 6. The Impact Of Gender-Responsive Energy Policies On Macroeconomic Outcomes -- 7. Women In The Transport Sector: From Mobility To The Profession -- Part III Women's Empowerment and Barriers -- 8. Women's Empowerment And Leadership: Barriers And Perspectives -- 9. Considering Gender Lens In The STEM Field -- 10. Gender-Based Violence: Basics And Evolution -- Part IV Monitoring Economic Development Toward a Just Transition -- 11. The Benefits of Considering Gender in Economic Development -- 12. Disaggregating Data by Sex and Gender to Enable Inclusive Digital and Green Transitions in Ethiopia, India and the USA -- 13. Concluding Chapter: Reimagining a Green and Digital World.
Keywords: Sex; Sustainability; Bioclimatology; Science -- Social aspects; Feminism; Feminist theory; Gender Studies; Sustainability; Climate Change Ecology; Science and Technology Studies; Feminism and Feminist Theory